Real time implementation of adaptive line enhancer - Darghaoth, Ahmed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The contamination of a desired signal by noise (undesired signal) is a main problem encountered in many applications. The digital filters with fixed coefficients exhibit satisfactory performance in cancelling the noise when the desired signal has stationary characteristics. However, when the desired signal has changing characteristics, there may be a performance degradation in eliminating the noise by a digital filter with fixed coefficients. As a remedy to this, adaptive noise cancellation method is used. In the adaptive noise cancellation method, the coefficients of the digital filter are updated by using an adaptive algorithm, until a minimum error is obtained. In this thesis, the principles of adaptive noise cancellation have been studied by using an adaptive line enhancer (ALE) configuration. The ALE configuration is simulated by using Simulink of Matlab and is implemented by using a digital signal processor (TI TMS320C6416T) in real time. The performance of ALE under different signal to noise ratio, number of filter coefficients, and step size of the adaptive algorithm has been studied extensively. When step size is small it leads to a good estimation of the sinusoidal signal, but the convergence speed slows down. The ALE output becomes more accurate when more coefficients are used in the filter. When SNR value is increased the estimation becomes more successful resulting in a small error at the ALE output. Keywords: Adaptive Filters, Adaptive Noise Cancellation, Least Mean Square Algorithm, Adaptive Line Enhancer, Signal to Noise Ratio. ………………………………………………………………………………………………………………………… ÖZ: Birçok uygulamada, istenen bir sinyalin gürültü tarafından kirlenmesi karşı karşıya kalınan bir problemdir. İstenen sinyalin durağan bir yapısı olduğu durumda, sabit katsayılı sayısal süzgeçler gürültüyü yok etmek için yeterli bir performans sergilerler. Bununla birlikte, istenen sinyalin durağan bir yapısı olmadıgı durumda, sabit katsayılı sayısal süzgeçler gürültüyü yok etme işleminde bir performans azalması ortaya çıkmaktadır. Bu probleme çare olarak, uyarlanabilir gürültü yoketme metodu kullanılır. Uyarlanabilir gürültü yoketme metodunda, sayısal süzgeçin katsayıları uyarlanabilir bir algoritma vasıtasıyla hata sinyalinin değeri minimum olana kadar güncellenmektedir. Bu tezde, uyarlanabilir gürültü yoketme metodunun prensipleri uyarlanabilir kanal yükselticisi kullanarak çalışılmıştır. Uyarlanabilir kanal yükselticisinin Matlab'ın Simulink ortamında benzetimi yapılmış ve buradaki Simulink modeli sayısal sinyal işlemcisine (TI TMS320C6416T) yüklenerek, gerçek zamanda Matlab'dan bağımsız olarak kendi başına çalışması sağlanmıştır. Uyarlanabilir kanal yükselticisinin farklı sinyal gürültü oranı, süzgeç katsayı sayısı, ve uyarlanabilir algoritmanın adım büyüklüğü altındaki performansı ayrıntılı olarak çalışılmıştır. Adım büyüklüğü küçük olduğu zaman, istenen sinüs sinyalinin kestirimi iyi olur, fakat yakınsama hızı yavaşlar. Süzgeçteki katsayıların sayısı artırıldıkça, ALE çıkışı (istenen sinüs sinyali) daha doğru olar. Sinyal gürültü oranı artırıldıkça, sinyal kestirimi daha başarılı olur ve ALE çıkışındaki hata sinyalinin küçülmesine neden olur. Anahtar Kelimeler: Uyarlanabilir Süzgeçler, Uyarlanabilir Gürültü Yoketme, Enaz Ortalama Kare Algoritması, Uyarlanabilir Kanal Yükselticisi, Sinyal Gürültü Oranı.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Prof. Dr. Hasan Kömürcügil.
Keywords: Computer Engineering; Signal Processing; Speech Recognition; Adaptive Filters, Adaptive Noise Cancellation, Least Mean Square Algorithm, Adaptive Line Enhancer, Signal to Noise Ratio